Akomodasi Nilai-Nilai Budaya Masyarakat Madura Mengenai Penyelesaian Carok Dalam Hukum Pidana - Mahrus Ali (Jurnal Hukum IUS QUIA IUSTUM, 2010)
This research focuses on the accomodation of cultural values of Maduranes society in solving carok problem in criminal law. Using the socio-legal research, interview, observation as the primery data, and data analysis are based on the inductive and qualitative manner, this research reveals that changing the criminal law conception as the public law into public law with the private dimension particularly in murder cases caused by self esteem defence is a must to give a chance for cultural values of Maduranes society in solving carok problem. So that, penal mediation based on the cultural values of Maduranes society as a methode to solve carok can be accomodated in criminal law by adopting some principles of traditional village or tribal moots model, victim-offender mediation model, and community panels or courts model.Key words : carok, cultural values, and penal mediation